Quartet : how four women changed the musical world - Broad, Leah, 1991- (Faber & Faber, 2023)
"Ethel Smyth (b. 1858): Famed for her operas, this trailblazing queer Victorian composer was a larger-than-life socialite, intrepid traveller and committed suffragette. Rebecca Clarke (b. 1886): The talented violist and Pre-Raphaelite beauty and one of the first women ever hired by a professional orchestra, later celebrated for her modernist experimentation. Dorothy Howell (b. 1898): A prodigy who shot to fame at the 1919 Proms, her popularity as the 'English Strauss' never dented her modesty; on retirement, she tended Elgar's grave alone. Doreen Carwithen (b. 1922): One of Britain's first women film composers -- who scored Elizabeth II's coronation film -- her success hid a twenty-year affair with her married tutor. In their day, these women were celebrities, composing groundbreaking music and pioneering creative careers. But today, they are ghostly presences in history, surviving only as muses and footnotes to male contemporaries like Elgar, Vaughan Williams and Britten -- until now. Leah Broad's stunning debut group biography resurrects these forgotten voices, recounting lives of rebellion, heartbreak and ambition -- and celebrating their music. Lighting up a panoramic sweep of British history over two world wars, Quartet revolutionises the classical canon forever." --